Characteristics and Prognostic Factors of Non-HIV Immunocompromised Patients With Pneumocystis Pneumonia Diagnosed by Metagenomics Next-Generation Sequencing - Duan, Jiali; Gao, Jing; Liu, Qiuhong; Sun, Mengfei; Liu, Yang; Tan, Yingshuai; Xing, Lihua (Frontiers in Medicine, 2022)
Objective: To evaluate the potential of metagenomic next-generation sequencing (mNGS) for the diagnosis of Pneumocystis pneumonia (PCP) in non-human immunodeficiency virus-infected patients. And to discuss the clinical characteristics and identify prognosis factors associated with non-HIV PCP patients. Methods: PCP patients who admitted in respiratory ICU between May, 2018 and May, 2020 were retrospectively reviewed, subjects were divided into survivor and non-survivor group according to patients’ outcome. Conventional methods and mNGS for detecting P. jirovecii were analyzed. And patients’ demographics, comorbidities, laboratory parameters and treatments were compared and evaluated in both groups to identify risk factors for mortality by using univariate and multivariate logistic regression. Results: Forty-six immunocompromised patients with PCP were enrolled in this study, mNGS showed a satisfying diagnostic performance of 100% positive of detecting P. jirovecii from BALF samples in all non-HIV PCP patients, compared to only 15.2% for GMS straining and 84.8% for Serum BDG. Among them, the mean age was 46.4-year-old (range 18~79-year-old) and mortality rate was 43.5%. The dominant underlying conditions were connective tissue diseases (34.8%), autoimmune kidney diseases (30.4%), followed by hematologic malignancies (10.9%) and solid organ transplantation (6.5%). None of them had previously received trimethoprim-sulfamethoxazole for PCP prophylaxis. Multiple infections were very common, over two thirds’ cases had mixed infections. Compared with survivors, non-survivors had a higher APACHE II score (14.4±4.8 vs.10±3.4), PCT [ng/ml：0.737(0.122-1.6)vs.0.23(0.095-0.35)], lactic dehydrogenase (LDH) [U/L：1372(825.5-2150)vs.739(490.5-956)] and neutrophil-lymphocyte ratio (NLR) [21.6(15.67-38.2)vs.11.75(5.1-15.52)], but had a lower PaO2/FiO2 ratio (mmHg:108.8±42.4vs.150.5±47.5), lymphocytes [×109/L：0.33(0.135-0.615)vs.0.69(0.325-1.07)]and CD4+ T cells [cell/μL：112(53.5-264)vs.255(145-303.5)], all P﹤0.05. What’s more, non-survivors’ PaO2/FiO2 ratio of day 3 and day 7 hadn’t improved when compared with day one’s, platelet level and NLR became worse. Multivariate analysis showed that pathogens’ co-infection (OR =9.011, 95%CI was 1.052-77.161, P=0.045) and NLR (OR =1.283, 95%CI was 1.046-1.547, P=0.017) were the independent risk factors for non-HIV PCP patients and resulted in death. Conclusion: mNGS is a very sensitive diagnostic tool for identifying P. jirovecii in non-HIV immunocompromised patients. PCP in non-HIV-infected patients is associated with a high rate of multiple infection and severe condition. Occurrence of mixed infection and elevation of NLR were the independent risk factors of poor prognosis.